THE EFFECT OF EXCHANGE RATE VOLATILITY ON UGANDA'S TRADE BALANCE - Shen, qianling; Orach, Henry; Chen, Pu; Wei, Shiying; Ssewajje, Hassan; Rose, Wigmore (Advances in Social Sciences Research Journal, 2021)
This study examines the long-run and the short-run relationship between the real exchange rate, GDP, FDI, inflation (INF), gross capital formation (GCF), Net official's development assistance (NODA), GNI, and trade balance in Uganda for the period 1994-2018. We used an Augmented Dickey-Fuller (ADF) test for the stationarity test, and we use the Johannsen cointegration approach to prove the existence of cointegration. The ADF tests show that the series was non-stationary in level but became stationary after the first difference. The Johannsen cointegration test indicates the long and short-run relationship between all the explanatory and trade balance in Uganda. Under such circumstances, a Vector Error Correction Model (VECM) is employed since the results offer more information than other data generation processes. Our findings are as follows: Real exchange rates, FDI, GCF and have a positive relationship with Trade balance. It means that Uganda can depreciate the Exchange rate to improve its Trade balance. The results proved the J-Curve effect's existence (i.e., the long-term impact of exchange rate on trade balance). The recommendations from this study are - Uganda's monetary policy management should emphasize more efforts on the stability and minimization of the volatility of exchange rates of the shillings since its movements affect international prices both negatively and positively, leading to either a decline or trade boost. Keywords: Trade balance; Real exchange rate; Net official's development assistances; GNI; VECM model; Uganda